Globalization and the Muslim State: Navigating Political, Economic, and Cultural Transformations in an Interconnected World - Muhammad Adil Iqbal; Ashfaq Ahmed; Nurul Izzati Haji Jamil (CV Media Inti Teknologi, 2026)
Background: Globally, political power, economic systems, and cultural identities are all being shaped by the transformative forces of globalization. Striking a balance between global integration and the preservation of sovereignty, Islamic values, and cultural heritage is a daunting task for countries with Muslim-majority populations.Objectives: The objective of this research is to critically analyze the ways in which globalization affects the political, economic, and cultural aspects of Muslim states and to pinpoint tactical avenues for participation that is both flexible and grounded in values.Methods: Using a thorough analysis of current academic literature, policy documents, and institutional reports, the study takes a qualitative, conceptual approach. Globalization Theory, World-Systems Theory, and Political Islam are integrated into a multifaceted analytical framework that directs the analysis.Results: The results show that Muslim governments actively participate in global networks and are not merely passive consumers of globalization. In terms of politics, they negotiate sovereignty within global governance frameworks; in terms of the economy, they are structurally dependent but exhibit innovation through the halal and Islamic finance sectors; and in terms of culture, they manage conflicts between Islamic identity and global influences by using hybrid and adaptive tactics. The primary contribution of the paper is an integrated analytical model that connects ideological and policy responses in the Muslim world with structural limitations.Conclusion: Adaptive governance, economic diversity, and culturally sensitive policymaking are necessary for effective engagement with globalization. By utilizing their normative frameworks, Muslim governments can improve their standing internationally while preserving their strategic independence.